Relationship between skeletal malocclusion and chin soft tissue thickness in patients at a dental hospital: a cross-sectional study - safira, Sharah; Darwis, Rudi; Tammama, Tichvy (Universitas Padjadjaran, 2025)
Introduction: Facial aesthetics significantly influence an individual's appearance and attractiveness. The chin is a crucial component of facial profile and personality. Lateral cephalometric radiography is frequently employed to assess the balance between skeletal structure and soft tissue, aiding in facial profile analysis, orthodontic diagnosis, and treatment planning. This study aimed to analyze the relationship between skeletal malocclusion and chin soft tissue thickness in patients at a Dental Hospital. Method: A cross-sectional study was employed. The research population comprised lateral cephalograms of orthodontic patients aged 15–28 years, taken at Unjani Dental Hospital between January 2018 and December 2023. A total of 81 cephalograms were selected using consecutive sampling, based on predefined inclusion and exclusion criteria. These cephalograms were categorized into three malocclusion groups (Angle Class I, II, and III). Soft tissue thickness at the chin was measured from the skeletal to the soft tissue at the Pogonion (Pog-Pog'), Gnathion (Gn-Gn'), and Menton (Me-Me') points. Data were analyzed using ANOVA and the Kruskal-Wallis test. Results: The average chin soft tissue thickness at the Pogonion point was greatest in Class II malocclusion (13.38 mm) compared with Class I (13.14 mm) and Class III (13.03 mm). Similarly, the greatest average thickness at the Gnathion point was also observed in the Class II malocclusion group. The ANOVA test yielded a p-value of 0.991 for Gnathion, while the Kruskal-Wallis test showed p-values of 0.918 for Pogonion and 0.698 for Menton. Conclusion: There is no relationship between skeletal malocclusion and chin soft tissue thickness among patients at a dental hospital.